ANALYSIS OF MACHINE LEARNING AND AI TO ENHANCE MARKETING NEEDS AND CUSTOMER SATISFACTION - Nugroho, Dony Ari (International Journal of Social Service and Research, 2024)
The development of Machine Learning (ML) and Artificial Intelligence (AI) technologies has revolutionized various industries, including marketing and customer satisfaction. In the modern competitive business era, companies are increasingly relying on this technology to improve operational efficiency and effectiveness, especially in answering marketing needs and customer satisfaction. This study aims to analyze the role of ML and AI in strengthening aspects of marketing and customer satisfaction in the business sector. The research method uses a qualitative approach with data collection techniques through literature studies. After the data is collected, it is then analyzed by the stages of filtering relevant data, presenting key information, and answering the research objectives in the conclusion. The results of the study show that the application of ML and AI can significantly improve the marketing effectiveness of companies through personalization of products and services, conducting more accurate customer segmentation, predicting consumer behavior, and optimizing various aspects of marketing. On the other hand, the application of ML and AI also plays an important role in improving customer satisfaction. For example, with the use of intelligent chatbots and customer feedback analysis, companies can understand the shortcomings that need to be fixed, then improve the quality of customer service. So, by utilizing this technology, companies can increase efficiency in marketing, drive increased sales, and build more solid relationships with customers, which ultimately contributes to increased customer satisfaction.